Taking Sides / Clashing Views in Abnormal Psychology: Fourth Edition - Halgin Richard P (Mcgraw Hill - Contemporary Learning Series, 2007)
A debate-style reader designed to introduce students to controversies in abnormal psychology. Psychological Conditions and Treatments, Should Individuals with Anorexia Nervosa Have the Right to Refuse Life-Sustaining Treatment?, Is Psychological Debriefing a Harmful Intervention for Survivors of Trauma?, Are Blocked and Recovered Memories Valid Phenomena?, Is Multiple Personality Disorder a Valid Diagnosis?, Does Attention Deficit Disorder Exist?, Should All Uses of MDMA (Ecstasy) Be Prohibited?, Should Abstinence Be the Goal for Treating People with Alcohol Problems?, The Trend Toward Biological Interventions, Are Prozac and Similar Antidepressants Safe and Effective?, Are Antipsychotic Medications the Treatment of Choice for People with Psychosis?, Is Ritalin Overprescribed?, Should Psychologists Prescribe Medication?, Is Electroconvulsive Therapy Ethical?, Social Issues, Is Sexual Orientation Conversion Therapy Ethical?, Does Exposure to Media Violence Promote Aggressive Behavior?, Is Pornography Harmful?, Is Divorce Always Detrimental to Children?.